Equações integro-diferenciais de ordem fracionária - Souza, Ana Paula Dantas de (2013)
In this work we demonstrate a theorem obtained by C. Cuevas e J.C. de Souza, which establishes the existence and uniqueness of mild solution S-asymptotically !-periodic for a semilinear fractional equation. In addition, we discuss an application of this problem for a partial differential equation of fractional order. This article was published in 2008 in Applied Mathematics Letters, as the title S-asymptotically !-periodic solutions of semilinear fractional integro-differential equations.